CTA Experience: sharing information and knowledge to improve food and nutrition security in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Presentation on theme 2: Information Needs for Improved Decision Making about Food and Nutrition Security